2015
DOI: 10.1159/000370002
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer: Hidden Pathology in a Patient with Abnormal Uterine Bleeding and Known Leiomyoma

Abstract: Uterine leiomyomas and endometrial pathology are both associated with abnormal uterine bleeding. We report a case in which a nulliparous woman with heavy uterine bleeding and leiomyomas had undergone two prior hysteroscopic myomectomies for benign leiomyomas. She was evaluated, but was ineligible for a clinical trial of a novel Magnetic Resonance guided High Intensity Focused Ultrasound (MRg​HIFU) device. The 8 cm, prolapsed submucosal leiomyoma hindered endometrial sampling and was inaccessible to HIFU treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…These processes are likely guided, in part, by regulatory mechanisms of miRNAs, that when dysregulated, as can occur in psychosocial stress-related exposure, may induce cancer-related pathways in the myometrium that contribute to broid development [38]. Corroborating these ndings, we found the most signi cant KEGG pathways enriched by social stress-associated miRNA-mRNA targets were at pathways relevant to reproductive tumorigenesis, including endometrial cancers, which have been observed concurrently in those with broids [39], and p53 signaling, a fundamental signaling pathway required for broid growth [40], as well as pathways in the endoplasmic reticulum (ER) and proteoglycans. Indeed, broids exhibit a higher abundance and swelling of the ER [37] and contain different composition of proteoglycans within extracellular matrix deposits [41].…”
Section: Discussionsupporting
confidence: 61%
“…These processes are likely guided, in part, by regulatory mechanisms of miRNAs, that when dysregulated, as can occur in psychosocial stress-related exposure, may induce cancer-related pathways in the myometrium that contribute to broid development [38]. Corroborating these ndings, we found the most signi cant KEGG pathways enriched by social stress-associated miRNA-mRNA targets were at pathways relevant to reproductive tumorigenesis, including endometrial cancers, which have been observed concurrently in those with broids [39], and p53 signaling, a fundamental signaling pathway required for broid growth [40], as well as pathways in the endoplasmic reticulum (ER) and proteoglycans. Indeed, broids exhibit a higher abundance and swelling of the ER [37] and contain different composition of proteoglycans within extracellular matrix deposits [41].…”
Section: Discussionsupporting
confidence: 61%
“…30 A recently published case report detailed an occult endometrial cancer found on the endometrial side of a prolapsing fibroid in a premenopausal patient with a known fibroid history. 41 No endometrial sampling was performed due to obstruction of the cervical canal by the leiomyoma as well as the attribution of her symptoms to her known fibroid. The authors recommended …”
Section: Risk Factorsmentioning
confidence: 99%
“…These processes are likely guided, in part, by regulatory mechanisms of miRNAs, that when dysregulated, as can occur in psychosocial stress-related exposure, may induce cancer-related pathways in the myometrium that contribute to fibroid development [ 38 ]. Corroborating these findings, we found the most significant KEGG pathways enriched by social stress-associated miRNA-mRNA targets were at pathways relevant to reproductive tumorigenesis, including endometrial cancers, which have been observed concurrently in those with fibroids [ 39 ], and p53 signaling, a fundamental signaling pathway required for fibroid growth [ 40 ], as well as pathways in the endoplasmic reticulum (ER) and proteoglycans. Indeed, fibroids exhibit a higher abundance and swelling of the ER [ 37 ] and contain different composition of proteoglycans within extracellular matrix deposits [ 41 ].…”
Section: Discussionmentioning
confidence: 72%